WET WEIGHT AND NUMBER OF THE ELEPHANT GRASS TILLER ARE PLANTED WITH SOYBEAN INTERCROPPED - Suharno, Ben; Puspitaningrum, Dewi (BIOMA, 2011)
This study aims to investigate: the influence of the number of participants crop (soy-bean), the influence of Rhizobium sp dosage, interactions influence the number of participants crop (soybean) and Rhizobium sp dose to the total wet weight and num-ber of tiller Pennisetum purpureum, the planting of grass-soybean intercropping Rhi-zobium sp inoculation. The research method uses randomized full factorial (factorial RCBD) with 2 factors and 3 replications. Parameters to be measured is the total wet weight and number of tiller Pennisetum purpureum. The data obtained were analyzed by analysis of vari-ance, followed by Duncan multiple range test and multiple linear regression ana-lysis. The results showed that treatment of soybean plants participant, dose Rhizobium sp, and participant interaction with defoliation of soybean Rhizobium doses of 1 and 2 did not significantly affect the total wet weight and number of tiller Pennisetum pur-pureum. However, in the second defoliation, Rhizobium dose significantly influence the total wet weight of Pennisetum purpureum. The conclusion is, cropping the grass-soybean intercropping with inoculation of Rhi-zobium sp can not be used to increase the total wet weight and number of grass tiller.Key words: Pennisetum purpureum, wet weight, tiller, Rhizobium sp, soybeans.